Establishment of a school for the hearing impaired in NCR - Almada, Aleli Glaiza (College of Engineering, 2005)
Every individual has the right to a quality education. and every child with special needs has right to an educational program suited to his needs. Awake, Learn and Respect Center for the Hearing Impaired (ALR) would address these needs of special children ,specifically the hearing impaired. The proponents of this study believe that these individuals are capable of being independent and useful in the society provided that they are given the proper guidance and education, these individuals would be able to develop their abilities to its maximum potential. In line with the government's mission of providing quality education to everyone, the project was conceptualized and has been studied. The project also hopes to reach the consciousness of the general public that they may be aware of the importance of providing education to individuals with special needs. The proponents of the study hopes that in the years to come, this group in the society would be treated more favorably and accordingly and that, more services would be provided to address their needs. The objective of the study is to determine the feasibility of a center that deals with the pre-elementary and complete elementary educational and special needs of the physically challenged children, especially the hearing impaired, here in the Philippines. This will be done through innovating current teaching methods, practices, facilities and equipment used by existing special education school today. Awake, Learn and Respect center for the Hearing-Impaired is situated in Sacred Heart Village, Brgy. Bagbaguin, Valenzuela City. This site is chosen based on accessibility, environment, and cost of land and opportunities for expansion. The service will be provided in Metro Manila. And ALR would be catering to the population with annual income of 100,000 pesos and above. The main users of the service are hearing-impaired children ages 3-14. The demand or the services was determined through the use of the data gathered on population from the National Statistics Office. It is evident from this information that there is a need for a special education school for the hearing-impaired. Also, most schools providing education to special children today are public or government owned and thus, may not be giving the proper education needed by these special children. With the continuous growth of the Philippines population, the difference between the demand and supply become greater assuming that establishment of special education schools would remain at the same rate today as with the coming years. Thus, this difference becomes irreconcilable. It was then concluded from the analysis of the market the the project is feasible. The manpower, materials, equipment and program requirements in establishing a special education school for the hearing-impaired was analyzed. All services and materials to be provided and utilized by the school are in accordance to the requirements set by the Department of Education. From the analysis, the project was determined to be technically feasible. After considering the financial aspect of the project such as financing needs and financial projections, the project can sustainably operate, cover its expenses and at the time serve satisfactorily its functions and goals. Awake, Learn and Respect Center for the Hearing Impaired would require Php9,916,427.62as its project cost. The bulk of the initial investment cost will be financed through grants from international funding organization and the rest will be solicited from private and corporate donors. It is the department of Education's regulation that a special education school under a non-stock non-profit corporation. Expenses and capital in this type of organization is shared by a group of individuals called the incorporators. Management of the school would be handled by these individuals with a reshuffling of positions after a certain period. As a whole, the project has been proven to be feasible and it is evident that it will make a good contribution to society. Although the project has been proven to be feasible and it is evident that it will make a good contribution to society. Although the project may not be very profitable in terms of investment returns, its profitability can be measured with each successful child it helped.